A health belief survey among Kuwaiti parents on human papillomavirus vaccination - Ahmad Abuzoor; Dr Cyril Eshareturi; Dr Melissa Owens; Rae Nesbitt; Drs Cor Jonker (International Journal of Infectious Diseases)
Introduction: In Kuwait, human papillomavirus (HPV) vaccination is available in the private healthcare sector and only upon request from governmental facilities. To design a health promotion campaign to accompany the introduction of an official national HPV vaccination programme, a survey was conducted with a representative multistage sample of 534 Kuwaiti parents/guardians of children eligible for vaccination, corresponding to a response rate of 89%. The aim of the study was to ascertain the health beliefs of the Kuwaiti population regarding HPV and HPV vaccination. Methods: Survey questions were structured to assess parents’ scores on knowledge and the health belief model (HBM) concepts of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues-to-action (Champion & Skinner, 2008), as well as the intention to vaccinate. Results: Statistically significant links between scores for knowledge and scores of HBM concepts, and between scores of HBM concepts and vaccination intention, show the HBM model can be used to model HPV vaccination promotion campaigns. Most respondents had poor knowledge of HPV and HPV vaccination, were 55.6% (n = 297), 24.9 % (n = 133), and 19.5 % (n = 104) for poor, fair, and good knowledge of HPV and vaccination, respectively. Parents of daughters were more likely to have a higher perception of barriers to vaccination, had lower scores of perceived severity of HPV infection, were more likely to respond to cues-to-action for vaccination, and lower scores for perceived benefits of HPV vaccination, and scored lower on perceived susceptibility, even though fathers were more likely to believe their daughters were at risk. The results showed that HPV vaccination has a stigma of promiscuity attached, even though many parents were willing to accept vaccination if officially recommended. Discussion: Our study showed the importance of different health beliefs about HPV and HPV vaccination regarding daughters versus sons. However, A study by Alsanafi et al. (2023) showed that Kuwaiti female university students have little knowledge of HPV and of the vaccine, with vaccine conspiracy beliefs negatively influencing their willingness to vaccinate. This study corroborates some of our findings. Similarly, a study among Syrian mothers showed that they had little knowledge and negative responses towards HPV vaccination, primarily due to lack of information, fear of side effects, and distrust of health authorities (Al Saad and Jadoo 2018). Conclusion: Any HPV vaccination promotion campaign in Kuwait should address the lack of knowledge, the stigma of promiscuity, perceived barriers, such as misconceptions regarding side-effects of the vaccination, and other health beliefs of parents. Importantly, it should use the trust that parents place in Kuwaiti health authorities and especially the evidence that parents of daughters would be more open to cues-to-action to vaccinate.